ASEAN Policy Responses to COVID-19 Pandemic: Adaptation and Experimentation Policy: A Study of ASEAN Countries Policy Volatility for COVID-19 Pandemic. (March 2022) - Purnomo, Eko Priyo; Agustiyara,; Nurmandi, Achmad; Dewi, Arlina; Rosa, Elsye Maria; Bayu, Agung Huda; Erviana, Rima
In response to the COVID-19 pandemic, this paper provides valuable information to establish new comparative policies between ASEAN countries. The study used disproportionate policy-making that stimulated the understanding of different adaptive strategies. The paper identified the extent of government response policy as a range of proportionate public involvement. The measure of disproportionality was obtained by calculating the regional differentiation in a particular country's average response to a crisis. This study found that six ASEAN countries are disproportional in their Policy Response to the COVID-19 Pandemic. Thailand is ranked the highest and classified as the most prepared country in terms of Global Health Security, and four countries are classified as normo-action. Indeed, Thailand is one of the countries with the most-prepared health security. Nonetheless, countries deemed less prepared and underreacting include Laos, Cambodia, Malaysia, Singapore, Indonesia, Myanmar, and the Philippines, which have all witnessed continuous rapid growth in COVID-19 infections.